Anastral Spindle Assembly: A Mathematical Model - Hallen, Mark A. (The Biophysical Society, 2009)
Assembly of an anastral spindle was modeled as a two-stage process: first, the aggregation of microtubule foci or asters around the chromosomes, and second, the elongation of cross-linked microtubules and onset of bipolarity. Several possibilities involving diffusion and transport were investigated for the first stage, and the most feasible was found to be binding of the asters to cytoskeletal filaments and directed transport toward the chromosomes. For the second stage, a differential-equation model was formulated and solved numerically; it involves cross-linking of microtubules with those aligned with the spindle axis and between microtubules bound to different chromosomes, and sliding of microtubules along the spindle axis to elongate the spindle. Ncd was postulated to perform both functions. The model shows that spindle formation begins with rapid cross-linking of microtubules, followed by elongation, which continues until the population of microtubules aligned with the spindle axis is depleted and microtubules cross-linking different chromosomes dominate. It also shows that when sliding is inhibited, short bipolar spindles still form, and if clustering is enhanced, normal-length spindles can form, although requiring longer assembly time. These findings are consistent with spindle assembly in live wild-type and ncd mutant Drosophila oocytes.